Consolidating role of historical memory in formation the moral foundations of modern Ukrainian society - Liudmyla Ovsiankina (Cхід, 2019)
The article is devoted to the analysis of the consolidating role of historical memory in forming the moral principles of modern Ukrainian society. The significance of historical memory in the development of the collective consciousness of the Ukrainian nation, the translation of all spiritual experience - knowledge of higher moral values: goodness, truth, beauty, love for freedom and justice - to the next generations is highlighted. Man and people in general are considered as the main bearers, actors and creators of historical memory. It is analyzed that the best ethical examples are created in national history as certain ways of comprehension of national interests. They are firmly fixed in historical memory and go to the historical arena in a dialectical progression - in a new form, taking into account the modern conditions of life, new pragmatic knowledge, technologies and ideas that each new generation produces.